2023
DOI: 10.3390/foods12214045
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant Activity, Bioaccessibility, and Thermal Stability of Encapsulated Strawberry Fruit (Fragaria × ananassa) Polyphenols

Faith Seke,
Oladipupo Q. Adiamo,
Yasmina Sultanbawa
et al.

Abstract: Bioactive compounds in red fruits, such as strawberries, are vulnerable to digestion, and encapsulation has become an alternative for their protection. This study aims at encapsulating strawberry juice (SJ) by freeze-drying with pea protein and okra mucilage (SJPO), pea protein and psyllium mucilage (SJPP), and pea protein, psyllium mucilage, and okra mucilage (SJPPO) and investigating the in vitro release. The highest encapsulation efficiency was observed in capsule SJPPO (95.38%) and the lowest efficiency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…[8], carbohydrates (maltodextrins and cellulose derivatives) [9], or lipids (waxes, emulsifiers) [10]. Seke et al [11] found that the stability and bioavailability of bioactive components in red fruits (such as strawberries) can effectively be improved by microencapsulation. According to Berg et al [12], microcapsules with the addition of highly esterified citrus pectin and beet pectin based on maltodextrin-encapsulated blueberry anthocyanin resulted in higher hydration capacity and better retarding of anthocyanin.…”
Section: Introductionmentioning
confidence: 99%
“…[8], carbohydrates (maltodextrins and cellulose derivatives) [9], or lipids (waxes, emulsifiers) [10]. Seke et al [11] found that the stability and bioavailability of bioactive components in red fruits (such as strawberries) can effectively be improved by microencapsulation. According to Berg et al [12], microcapsules with the addition of highly esterified citrus pectin and beet pectin based on maltodextrin-encapsulated blueberry anthocyanin resulted in higher hydration capacity and better retarding of anthocyanin.…”
Section: Introductionmentioning
confidence: 99%
“…Wild strawberry, scientifically known as Fragaria vesca, is a member of the Rosacea family and is usually found in Europe, Asia West of the Urals, and North America [12][13][14]. This plant species has a rich history in traditional medicine, where it has been widely recognized for its anti-inflammatory properties and its potential in the treatment of gastrointestinal disorders [4,11,12,15].…”
Section: Introductionmentioning
confidence: 99%